2018
DOI: 10.7759/cureus.2923
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Herpes Zoster Presented with Lower Limb Paresis

Abstract: Herpes zoster is a common viral disorder that typically shows characteristic painful skin lesion. Motor neuropathy rarely complicates herpes zoster infection, and it may be overlooked without suspicion. Here, we report a case of a herpes zoster patient who presented with sciatica and paresis, but without the typical skin lesion. The patient was initially misdiagnosed as having other disorders including trauma or spine lesion. Electrodiagnostic study and magnetic resonance imaging (MRI) helped to make an accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Skin lesions generally precede the neurologic symptoms by several days to one week. Some studies reported that in some rare incidents, neurologic symptoms occurred before skin lesions [1][2][3][6][7][8] . The patient in our case also experienced neuralgia followed by skin lesions occurring one week later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin lesions generally precede the neurologic symptoms by several days to one week. Some studies reported that in some rare incidents, neurologic symptoms occurred before skin lesions [1][2][3][6][7][8] . The patient in our case also experienced neuralgia followed by skin lesions occurring one week later.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes zoster (HZ) commonly presents with vesicular eruption due to the reactivation of varicella-zoster virus (VZV), especially in elderly patients [1][2][3][4][5]9) . Approximately 50% of HZ in the United States occurs in people 50 or older.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of C3-C5 motor nerves could lead to diaphragmatic paresis and induce the clinical manifestations, including dyspnea and pulmonary dysfunction (42,43). The affected ganglion segments and possible clinical manifestation are summarized in Table 1 (3,7,28,34,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Clinical Characteristics Of Szpmentioning
confidence: 99%
“…In addition to EMG, MRI examination also has relatively high sensitivity in detecting the involved nerves and muscles. Various previous studies have described the widening of the affected nerve and T2-weighed highsignals (63,69). The enhanced scanning through gadolinium (Gd)-contrast agents could also help to detect the inflammation levels of the involved nerve roots 9).…”
Section: Diagnosis and Auxiliary Examinations Of Szpmentioning
confidence: 99%